Are there differences between 1RM loads determined in isolated tests vs. In three different sequences? - de Carli, João Paulo Costa [UNESP]; Figueira, Thiago Gomes; Magosso, Rodrigo Ferro [UNESP]; Neto, José Campanholi [UNESP]; de Souza, Gabriella Soares; Perez, Sergio Eduardo de Andrade; Baldissera, Vilmar [UNESP] (My University, 2016)
This study determined if there are changes in 1RM load of 8 exercises performed as isolated tests or in three different orders of execution. The subjects consisted of 10 male volunteers (age, 23.1 ± 3.3 yrs; height, 180.0 ± 6.9 cm; body weight, 81.6 ± 13.1 kg; BMI, 25.1 ± 3.2 kg·m-2; body fat, 14.7 ± 5.2%) who had at least three months of resistance training experience. The tests were made on the following exercises: (a) bench press; (b) leg press; (c) triceps extension; (d) knee extension; (e) lat pull-down; (f) half squat; (g) biceps curls; and (h) leg curl. A one-way ANOVA (Sphericity Assumed) for repeated measures with 1RM loads in the four tests was used to determine the level of significance, and the intra-class correlation coefficients (ICC) were determined for the four 1RM loads. The significance level was set at P < 0.05. Results showed no significant differences between in 1RM loads in any of the exercises or sequences (P < 0.05). The findings indicate that there are no differences between these methods, and that a sequence with 8 exercises can be performed to determine 1RM loads.
Keywords: 1RM test; Exercise order; Resistance exercises